Organic semiconductors for visible light communications. (17th April 2020) - Manousiadis, Pavlos P.; Yoshida, Kou; Turnbull, Graham A.; Samuel, Ifor D. W.
Abstract : Organic semiconductors are an important class of optoelectronic material that are widely studied because of the scope for tuning their properties by tuning their chemical structure, and simple fabrication to make flexible films and devices. Although most effort has focused on developing displays and lighting from these materials, their distinctive properties also make them of interest for visible light communications (VLCs). This article explains how their properties make them suitable for VLC and reviews the main uses that have been explored. On the transmitter side, record white VLC communication has been achieved by using organic semiconductors as colour converters, while direct modulation of organic light-emitting diodes is also possible and could be of interest for display-to-display communication. On the receiver side, organic solar cells can be used to harvest power and data simultaneously, and fluorescent antennas enable fast and sensitive receivers with large field of view. This article is part of the theme issue 'Optical wireless communication'.